CANDIDE, un modèle économétrique - Waslander, H. (L'Actualité économique, 1975)
AbstractThis introductory text deals in very general terms with CANDIDE and development and application of large models.A brief sketch of the history of CANDIDE precedes a discussion of the extensive disaggregation and medium-term nature of CANDIDE; the two characteristics that set it apart from more traditional models.From his experience with CANDIDE the author then comments on model design and model use. Development of multi-purpose models, in his view, consists of many difficult and often arbitrary choices. He warns against excessive disaggregation, and use of models as black boxes. Finally, he calls for co-ordination of impact studies.